Functional analysis of the short splicing variant encoded by CHI3L1/YKL-40 in glioblastoma - Shi, Mengqi; Ge, Qianyun; Wang, Xinrong; Diao, Wenbin; Yang, Ben; Sun, Sipeng; Wang, Guohui; Liu, Tian; Chan, Andrew Man-Lok; Gao, Zhiqin; Wang, Yi; Wang, Yubing (Frontiers in Oncology, 2022)
The glycoprotein YKL-40 has been well studied as a serum biomarker of prognosis and disease status in glioblastoma. YKL-40 is a chitinase-like protein with defective chitinase activity that plays an important role in promoting cell proliferation, migration, and metastasis in glioblastoma multiforme (GBM). The short variant (SV) of YKL-40, generated by an alternative splicing event that splices out exon 8, was reported in the early developing human musculoskeletal system, although its role in GBM is still unknown. Our results showed that individual glioblastoma cell lines displayed increased expression of the short variant of YKL-40 after low serum treatment. In addition, unlike the full-length (FL) version, which was localized to all cell compartments, the short isoform could not be secreted and was localized only to the cytoplasm. Functionally, FL YKL-40 promoted cell proliferation and migration, whereas SV YKL-40 suppressed them. Transcriptome analysis revealed that these opposing roles of the two isoforms may be modulated by differentially regulating several oncogenic-related pathways, including p53, the G2/M checkpoint, and MYC-related signaling. This study may provide new ideas for the development of targeted anti-YKL-40 therapy in GBM treatment.